Візуалізація дефектів кремнієвих фотоелектричних сонячних батарей - Пахалюк, Р. І.; Божко, К. М. (НТУ "ХПІ", 2014)
В даній статті вперше вдалось поєднати в одному підході такі різні методи як інфрачервоні термографія та телевізійна мікроскопія для дослідження електролюмінісцентних дефектів. Основою підходу стала ідея нагрівання фотоелектричних сонячних батарей зворотним темновим струмом, в процесі якого і реалізовано візуалізацію дефектів. Застосовані нами методи візуалізації дефектів кремнієвих ФЕСБ базуються на процесі їх нагрівання зворотним темновим струмом. Візуалізація електролюмінісцентних дефектів дозволяє здійснювати контроль на основі ТЗВ.

Development of solar batteries becomes one of the priority directions of human development, but the high cost and lack of adequatemeans of control of defects in solar batteries at manufacturing and operation have become a serious problem, which in its turn, requires the development of new and improvement of already existing methods and means of control. This work is an attempt to summarize own experience of the authors of article in the development of methods and means of visualization of defects of solar batteries in the context of global developments. In this article, it became possible to combine such different methods as infrared thermography and television microscopy of electroluminescent defects in one approach for the first time. The basis of the approach was the idea of heating the photovoltaic solar batteries with reverse dark current, during which the visualization of defects is realized. This approach, based on the methods of visualization of defects, should accompany all lifetime of batteries - from manufacturing to the date of removing from operation, and lies in their complex application.
Visualization of defects of silicone photovoltaic solar batteries
Keywords: термографія; електролюмінісценція; перегрів; defect; thermography; electroluminescence; batteries; infrared visualization; overheating